Challenges to China's new stock market for small and medium-size enterprises: trading price falls below the IPO price - Guo, Haifeng; Wang, Tienan; Li, Yijun; Fung, Hung-Gay (Technological and Economic Development of Economy, 2014)
This study discusses the development of the Growth Enterprise Board (GEB), a part of the Shenzhen Stock Exchange (SZSE), which allows small and medium-size enterprises (SMEs) to raise capital on favourable terms by issuing shares in China. We use all initial public offerings (IPOs) in the GEB market to model the probability of the trading price for new issues that will fall below their IPO price from October 2009 to December 31, 2011. Three probability models (logit, probit and scobit models) are used. The results show that four important factors explain the probability of trading price falling below their IPO price. A high first-day turnover ratio, a small price update, an optimistic stock market, and high average initial returns of other firms prior to an IPO issue all reduce the risk that the trading price will fall below the IPO price. The stock market returns have a non-linear significant effect on that probability. Our results are useful for regulators, underwriters, and issuers in the development of the GEB market.